Consumers' Information-Seeking Behaviors on Dietary Supplements. (April 2020) - Nathan, Joseph P.; Kudadjie-Gyamfi, Elizabeth; Halberstam, Leah; Wright, Josephine T.
Background: Consumers are advised to seek information about dietary supplements (DS) before using them; little is known concerning whether this recommendation is heeded. Objective: The objectives of this pilot study were to investigate whether users of DS seek information about these products before using them and particularly whether such information is sought from health-care professionals (HCPs). Methods: Surveys administered face-to-face to adult consumers at three venues in New York City. Results: Between November 2017 and October 2018, 199 consumers were surveyed. Of the 139 (70%) DS users, 104 (75%) used at least one DS that was not prescribed/recommended by an HCP. Of those, 88 (85%) reported seeking information about DS before using them and two (2%) noted that for some they do and for some they do not. The source of information most frequently used was the Internet (76; 84%). Pharmacists, dietitians/nutritionists, and medical doctors were reported to be a source of information by seven (8%), six (7%), and five (6%) of the respondents, respectively. DS were most commonly purchased at a pharmacy (76; 54%). Of the 199 participants, 111 (56%) perceived DS to be "very safe" or "safe, " while 20 (10%) reported that DS were "unsafe" or "very unsafe"; 60 (30%) participants were "neutral." Conclusion: Although most DS users sought information prior to using them, the majority did so by using the Internet and only a few consulted with an HCP. HCPs should be proactive in educating consumers about the importance of consulting with them prior to using these products.